Toughening mechanism of coelacanth-fish-inspired double-helicoidal composites. (22nd March 2021) - Yin, Sha; Yang, Ruiheng; Huang, Yao; Guo, Weihua; Chen, Dianhao; Zhang, Wen; Ren, Mingwei; Zhou, Yujing; Xu, Jun
Abstract: The scales of coelacanth fish feature a rare double-helicoidal structure of collagenous fibrils, exhibiting great toughness. In this study, inspired by such biomaterials, engineering composite materials are designed and fabricated. Quasi-static three-point bending and Charpy impact tests are performed to evaluate their mechanical performance compared with the single-helicoidal counterparts (emulated from the Bouligand structure in Odontodactylus scyllarus ). Multiple delaminations are observed in the double-helicoidal composites, which preclude tensile crack propagation and then prolong the failure displacement; meanwhile, for single-helicoidal composites, the fiber architecture at the mid-plane serves as a vital role for hindering translaminar cracks propagation across the mid-plane. The dynamic energy absorption of double-helicoidal composites can reach 163.44 kJ m −2, 26.5% greater than that of the corresponding single-helicoidal samples, which is attributed to the more complex failure modes including fiber breakage and matrix cracking that both contribute to energy absorption. Double-helicoidal composites are not sensitive to fiber orientations on failure mode and such attribute enables more design freedoms. Additionally, the interlaminar stress is analyzed, and a greater value of the interlaminar stresses σ13 is discovered to be responsible for the delamination of double-helicoidal composites. Results reveal the underlying toughening mechanism of coelacanth-fish-inspired double-helicoidal composites and promote the next-generation impact-resistant composites design. Graphical abstract: Image 1 Highlights: Bio-inspired composite laminates were manufactured to mimic double-helicoidal structure of the coelacanth scale. Multiple delamination of double-helicoidal structure could prolong the failure displacement. The specific impact energy of double-helicoidal laminates outperforms greatly single-helicoidal ones. The greater value of interlaminar stress σ13 induces delamination of double-helicoidal composites.